On the nature of magnetic state in the spinel Co2SnO4. (30th March 2015) - Thota, S; Narang, V; Nayak, S; Sambasivam, S; Choi, B C; Sarkar, T; Andersson, M S; Mathieu, R; Seehra, M S
Abstract: In the spinel Co2 SnO4, coexistence of ferrimagnetic ordering below T N ≃ 41 K followed by a spin glass state below T SG ≃ 39 K was proposed recently based on the temperature dependence of magnetization M ( T ) data. Here new measurements of the temperature dependence of the specific heat C P ( T ), ac-susceptibilities χ ′( T ) and χ ″( T ) measured at frequencies between 0.51 and 1.2 kHz, and the hysteresis loop parameters (coercivity H C ( T ) and remanence M R ( T )) in two differently prepared samples of Co2 SnO4 are reported. The presence of the Co 2+ and Sn 4+ states is confirmed by x-ray photoelectron spectroscopy (XPS) yielding the structure: Co2 SnO4 = [Co 2+ ][Co 2+ Sn 4+ ]O4 . The data of C P versus T shows only an inflection near 39 K characteristic of spin–glass ordering. The analysis of the frequency dependence of ac-magnetic susceptibility data near 39 K using the Vogel–Fulcher law and the power-law of the critical slowing-down suggests the presence of spin clusters in the system which is close to a spin–glass state. With a decrease in temperature below 39 K, the temperature dependence of the coercivity H C and remanence M R for the zero-field cooled samples show both H C and M R reaching their peak magnitudes near 25 K, then decreasing with decreasing T and becoming negligible below 15 K. The plot of C P / T versus T also yields a weak inflection near 15 K. This temperature dependence of H C and remanence M R is likely associated with the different magnitudes of the magnetic moments of Co 2+ ions on the 'A' and 'B' sites and their different temperature dependence.